The Effect of Reinforcement Density on The Deflection of Reinforced Soil Retaining Wall - Zangana, Dhiaadin Bahaadin Noory (Nahrain University College of Engineering Journal, 2008)
This research involves the effect of both vertical and horizontal spacing, as well as the length of the reinforcing strips, on the structural behavior of a model reinforced soil retaining wall. The tests were carried out on a small-scale laboratory model, in which uniform graded sand was used as a fill material. It was placed at a high dense state; raining technique was used for this purpose. The sand was reinforced with thin dipped Aluminum strips. The size of these reinforcing strips was chosen sufficient enough to prevent rupture mode of failure. The retaining wall was presented by a plastic transparent sheet. The results showed that the horizontal spacing is more significant parameter on deflection of the wall as compared to the vertical spacing of the reinforcing strips. The critical values of the horizontal and vertical spacing with respect to this research were 20 and 10 cm respectively. A short length of reinforcement proved tocause appreciable deflection of the wall, even under close horizontal and vertical spacing